Analisis Efektivitas Dan Implementasi Motion Grafis Sebagai Media Informasi Untuk HSE Induction - Miranda Valen; Agung Riyadi (Politeknik Negeri Batam, 2022)
This research is about making motion graphics videos for information mediaHSE Induction at PT. Cameron Systems Batam. Based on e-form datavisits, there are 35% in one month the number of visitors who will work inPT. Cameron System Batam or there are 20-30 people in one month,with this amount, make a submission about HSE inductiondone continuously and takes a lot of time. Submission processinformation about previous HSE induction still using filepower point presentation, so the trainer must explain directlyto new employees or visitors, this step is less effective, so make ita new information media that is better in its delivery, namely,motion graphics videos. The use of motion graphics due to delivery throughillustrated motion pictures and videos are more attractive, effective andunlimited delivery compared to descriptive writing. OnThis research is in the manufacture of products, using the development methodvillamil molina, in this method there are five stages, namely development, pre-production, production, postproduction, then delivery. Then foranalysis of the effectiveness of motion graphics videos using the EPIC model methodwith dimensions of empathy, persuasiveness, impact, and communication. Resultsfrom this research in the form of a motion graphic video about HSE induction, the resultsanalysis using the EPIC model gets a value of 4.35 withthe very effective category means that the HSE induction motion graphics video is effectiveused for the delivery of HSE induction by the company